Capacity building models for managing multiple long-term conditions in low-and-middle-income countries: a systematic review and gap analysis - Abhinav Sinha; Krushna Chandra Sahoo; Pranab Mahapatra; Sandipana Pati; Jayasingh Kshatri; Srikanta Kanungo; Sandro R. Batista; Bruno P. Nunes; David Weller; Stewart W. Mercer; Sanghamitra Pati (Human Resources for Health)
Abstract Background The global prevalence of multiple long-term conditions (MLTCs) is increasing, challenging healthcare providers worldwide. In low- and middle-income countries (LMICs), healthcare professionals face additional obstacles in managing MLTCs due to the presence of disease-specific guidelines. This issue is exacerbated by the limited emphasis on both pre-service and in-service training of healthcare professionals on MLTCs within LMICs. Therefore, we conducted a systematic review to synthesize the scientific evidence on training and educational initiatives on MLTCs for health professionals in LMICs. Methods We conducted a search across PubMed, Embase, and CINAHL within the domains of ‘multiple long-term conditions’ and capacity-building and systematically reviewed the articles retrieved. The data were synthesized using a healthcare training framework that encompasses objectives, target audience, content and curriculum, training methodology, trainers and facilitators, logistics and implementation, participant engagement and satisfaction, and outcomes. Our findings were reported according to PRISMA guidelines. This systematic review was prospectively registered with the International Prospective Register of Systematic Reviews (CRD42022348483). Results Out of 15,981 initial records, 3614 duplicates were removed, leaving 12,367 for title and abstract screening. After full-text review of 204 articles, only four met the inclusion criteria—two from India, one from Ukraine, and one covering multiple African countries (South Africa, Uganda, Ethiopia, and Kenya) demonstrating a scarcity of literature in the field. These studies focused on increasing healthcare providers’ capacity to manage multiple chronic conditions through knowledge, skills, and competency-based training. A ‘train-the-trainer’ approach was emphasized for broader impact in low-income settings. Training methods varied, incorporating interactive sessions and interdisciplinary modular programs. Key recommendations included integrating updated curricula into medical education and addressing logistical barriers. While participants reported improved skills, challenges included sustaining support and adapting programs to local contexts. Conclusions MLTC-focused training in LMICs remains limited, with existing programs emphasizing competency-based learning and a ‘train-the-trainer’ approach. Key challenges include sustainability, logistical barriers, and local adaptation. Integrating structured, interdisciplinary training into medical education and professional development, alongside policy support and stakeholder collaboration, is important for future implementation.